Kinetics study of cellulose nanocrystals modification using rarasaponins by Elovich equation - Wijaya, Christian; Ismadji, Suryadi; Gunawan, Setiyo (IPTEK The Journal for Technology and Science, 2020)
The modification of cellulose nanocrystals (CNCs) using rarasaponins (RSs) was carried out to enhancing the hydrophobicity of the CNCs. The RSs are a natural surfactant that has hydrophilic and hydrophobic sides. The linked RSs on the CNCs surface can be used to bond the hydrophobic drugs so that the modified CNCs can be applied as the hydrophobic drugs carrier in the medical field. The kinetics study was successfully carried out using the Elovich equation as the modeling equation. The Elovich equation fits the modification results well based on two parameters, i.e., the RSs/CNCs ratios and the times. The dispersion characteristics analysis was carried out to figure the enhancement of the hydrophobicity on the modified CNCs compared to the unmodified CNCs. According to the kinetics study and the dispersion characteristics analysis, the modification of CNCs using RSs could enhance CNCs utilization in the hydrophobic drug delivery system